1996
DOI: 10.1128/mcb.16.7.3615
|View full text |Cite
|
Sign up to set email alerts
|

DNA Rearrangements Associated with Multiple Consecutive Directed Antigenic Switches in Trypanosoma brucei

Abstract: Changes in variant surface glycoprotein (Vsg) expression allow Trypanosoma brucei to elude the immune response. The expressed vsg is always located at the telomeric end of a polycistronic transcription unit known as an expression site (ES). Although there are many ESs, only one is active at any particular time. The mechanisms regulating ES transcription and switching are unknown. Chromosome rearrangements within or upstream of the ES have been described to occur in occasional switch events, but no changes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 54 publications
2
49
1
Order By: Relevance
“…Partial activation of ESs in bloodstream form T. brucei has been achieved before in experiments targeting drug resistance genes into "silent" ESs, although the levels of transcription were much lower than we show here (19,64). These low levels of transcription were "erased" after activation and subsequent inactivation of the partially active ES, implying the resetting of an epigenetic state (19).…”
Section: Up-regulation Of Silent Ess Correlates With a Block In Smentioning
confidence: 44%
“…Partial activation of ESs in bloodstream form T. brucei has been achieved before in experiments targeting drug resistance genes into "silent" ESs, although the levels of transcription were much lower than we show here (19,64). These low levels of transcription were "erased" after activation and subsequent inactivation of the partially active ES, implying the resetting of an epigenetic state (19).…”
Section: Up-regulation Of Silent Ess Correlates With a Block In Smentioning
confidence: 44%
“…In support of this notion, promoters from active or inactive ESs share the same sensitivity to DNase (24), and antigenic variation still occurs properly if the promoter of the active ES is replaced by the ribosomal promoter (41,42). Other arguments include the detection of transcripts originating from inactive ESs such as RNA transcribed from the ES beginning in procyclic forms (29), RNA from antibiotic-resistance genes inserted in inactive ESs (25), or RNA from different ESAG6 from inactive ESs, accounting for up to 20% of the total ESAG6 transcripts (28). Taken together these observations support the notion of leaky ES transcription (27).…”
Section: Discussionmentioning
confidence: 96%
“…Previous experiments pointed to mixed conclusions. On the one hand, transcripts from inactive ESs could be detected in bloodstream clones and even in procyclic forms, which do not express VSG, suggesting that transcription initiation takes place in all ESs simultaneously (22)(23)(24)(25)(26)(27)(28)(29). On the other hand, experiments tagging ESs with antibiotic-resistance genes showed that RNA expression can be detected from two ES, although the expression was unstable (30).…”
mentioning
confidence: 99%
“…VSG is the last gene in any BES, located less than 2 kb from the telomere and 40-60 kb downstream of the BES promoter [33]. T. brucei has multiple BESs (15-20 in the lister 427 strain used in this work), but only one is fully active, expressing a single type of VSG at any time [34,35].…”
Section: Introductionmentioning
confidence: 99%